Programmed Cell Death May Be Involved in the Seedless Phenotype Formation of Oil Palm - Htwe, Yin Min; Shi, Peng; Zhang, Dapeng; Li, Zhiying; Xiao, Yong; Yang, Yaodong; Lei, Xintao; Wang, Yong (Frontiers in Plant Science, 2022)
Oil palm (Elaeis guineensis Jacq.) is a well-known vegetable oil-yielding crop. Seedlessness is one of the most prominent traits in oil palm due to its low processing costs and high oil content. Nevertheless, an extensive study on molecular mechanisms regulating seedless phenotype formation in oil palm is very limited so far. In this study, stigma, style, and ovary from seedless and seeded (Tenera and Pisifera) oil palm trees were used to investigate the possible mechanism. Results showed that non-pollination resulted in no fruits, and self- and cross-pollinations resulted in seedless fruits, while boron treatment had no effect on seedless phenotype formation, implying that seedless trees have incomplete self and outcrossing incompatibility. Furthermore, the transcriptome data analysis highlighted eight programmed cell death (PCD) genes and three groups of PCD-related genes: 4-coumarate-CoA ligase (4CL), S-RNase, and MADS-box. The majority of these genes were significantly up-regulated in the stigma and style of Seedless palm trees compared to Tenera and Pisifera. In addition, the co-expression network analysis confirmed the significant correlation among these genes. Moreover, two simple sequence repeats (SSR) markers (S41 and S44) were developed to identify the seedless phenotype. The up-regulation of 4CL and MADS-box TFs activated the expression of PCD genes; on the other hand, S-RNase resulted in pollen tube RNA degradation and triggered PCD. While the link between PCD and seedless phenotype formation in oil palm has not been extensively studied to date, these findings suggest a role of PCD in pollen tube lethality, leading to double fertilization failure and the seedless phenotype.